PENGARUH STRATEGI DIFERENSIASI TERHADAP KEPUASAN KONSUMEN (KASUS HOTEL RATU MAYANG GARDEN PEKANBARU) - Sinaga, Dewi Sartika; Sutrisna, Endang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The issue of this research is the decline in the number of customer had visited and lodged Ratu Mayang Garden Hotel Pekanbaru in the last 3 years. This indicates the occurrence decrease in customers satisfaction so that customers switched to other hotels. The purpose of this study is to investigate the implementation of the strategy differentiation and determine customer satisfaction in Ratu Mayang Garden Hotel Pekanbaru. The collection of data through questionnaires to 100 customers Ratu Mayang Garden Hotel Pekanbaru. Results of a study of the strategy differentiation Ratu Mayang Garden Hotel considered is good. So also with the satisfaction of customers considered to be enough satisfaction. Results calculated with SPSS. Showed that the strategy differentiation (X) positive effect on customer satisfaction (Y) Ratu Mayang Garden Hotel Pekanbaru.Key words : Strategy Differentiation, Consumer Satisfaction, Ratu Mayang Garden Hotel Pekanbaru